The Effectiveness of Participatory Health Literacy Promoting Programs among Diabetes Risk Groups in Community, Thailand - Adisorn Wongkongdech; Jirachaya Kumchan; Chaloemporn Namyota; Souksathaphone Chanthamath; Ranee Wongkongdech (Asian Journal of Social Health and Behavior)
Introduction: The prevalence and incidence of diabetes are increasing worldwide. In Thailand, emphasis is placed on measures to enhance awareness of preventing the disease among high-risk groups and the general population. This study aims to determine health literacy (HL), health behavior patterns, awareness, and knowledge of diabetes prevention, and the effectiveness of promoting HL programs among diabetes risk groups in the Thai community. Methods: This study was designed for the research and development method and was conducted in April–October 2023. A cross-sectional study was conducted with 105 DRGs, selected using stratified random sampling from 10 villages. Data were collected through interviews and self-report questionnaires. In addition, a participatory program involving 43 stakeholders was designed to enhance diabetes prevention knowledge, using brainstorming sessions for activity planning, implementation, and evaluation. Pre- and post-test scores were analyzed using paired t-tests. Results: The analysis shows that nearly half of the DRGs are at a moderate level of HL, while the overall score falls below 55% of the total points. In addition, the health behavior patterns of the DRGs (3E2S) pose a risk for diabetes development. However, the results obtained from program utilization indicate that the potentiality for improved HL levels and promoting positive health behaviors are statistically significant (P < 0.001). Conclusion: Healthcare professionals, particularly within the primary healthcare system, should devise strategies to enhance HL and consistently implement programs targeting diabetes prevention in the community’s at-risk groups.